Vegetation Dynamics in the Unmul Samarinda Botanical Garden through Quantitative Analysis of Plant Distribution - Andrew Stefano; Sri Endayani (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
The Unmul Samarinda Botanical Garden (KRUS) holds a strategic role in the conservation of tropical biodiversity in East Kalimantan. This study specifically analyzes the dynamics of shrub, herbaceous, and tree vegetation using a quantitative approach through the quadrat method, which remains rarely applied comprehensively in conservation areas across eastern Indonesia. This research offers a novel approach by integrating vegetation structure metrics (including Shannon-Wiener, Pielou’s evenness, and Simpson’s dominance indices) with an assessment of environmental variables—such as soil pH, water supply, and light levels—within a spatial analysis based on ecological zoning. The results indicate that shrub and herbaceous vegetation tend to have a more even distribution, while trees exhibit clustered patterns, with overall high biodiversity levels (index >2.5). Tree vegetation is dominated by native Kalimantan species, whereas shrubs and herbs demonstrate greater species diversity, including the presence of invasive species. The practical contribution of this research includes providing a scientific foundation for KRUS management in formulating more adaptive and data-driven conservation strategies, particularly in mitigating invasive species. Furthermore, the findings may serve as a reference for sustainable green space planning in other tropical conservation areas and promote the integration of quantitative approaches into vegetation preservation policies.